Censored sociology: race, class and Social Science research in the Brazilian military dictatorship (1971-1977) - Trapp, Rafael (Revista de História, 2021)
What happens when an authoritarian State censors sociological research? This article addresses aspects of the relationship between scientific research on Blacks and the repressive configuration assumed by the State apparatus regarding its academic debate in the Brazilian military dictatorship. Three works in Social Sciences in São Paulo are analyzed, namely the master’s degrees of Edson Antonio Eustáquio (ELSP) and Eduardo de Oliveira e Oliveira (USP), and the Ph.D. of Eduardo Judas Barros (USP), studies that, respectively, disappeared, remained incomplete and were silenced. We sought to elaborate the hypothesis of repression of Social Science research on race and class during the 1970s as a form of censorship of critical thinking and its public discussion in Brazil. The scarcity of sociological research in this period was due to surveillance and effective repression by the State, protecting the official dogma of racial democracy.